DIFFERENCES IN SPECIES, COVERAGE AND DENSITY OF SEAGRASS IN THE INTERTIDAL AND SUBTIDAL AREAS AT LABAKKANG BEACH, PANGKAJENE ISLAND REGENCY - Indah Sandra Dewi; Lanuru, Mahatma; La Nafie, Yayu A; Amri, Khairul; Ukkas, Marzuki (Jurnal Ilmu Kelautan SPERMONDE, 2024)
Labakkang Beach, Pangkajene Islands Regency has the characteristics of gently sloping coastal waters covered with various mangrove and seagrass communities. In general, seagrass is more commonly found in intertidal than subtidal areas, this is due to the depth reason. However, based on first observations, seagrass in Labakkang coastal waters thrives in subtidal areas and is less fertile in intertidal areas. The purpose of this study was to decide the differences in species, cover, and density of seagrass in intertidal and subtidal areas in the waters of Labakkang Beach, Pangkajene Islands Regency. This research was conducted in July 2021 with the method used, namely purposive sampling. Measurements of environmental parameters at the sampling location were carried out directly (in situ) including temperature, salinity, tides, depth, and current velocity, while turbidity, Total Organic Matter (TOM) analysis, and grain size of sediment were carried out tegakanirectly (ex-situ). The results of the average measurements of temperature, salinity, current velocity, depth, turbidity and TOM respectively show the range of 300C - 310C; 33.3‰ – 35.0‰; 0.07 m/s - 0.18 m/s (at high tide); 0.31 m - 1.32 m; 11.06 NTU - 29.04 NTU and 2.49 % - 5.39 %. The results of sediment analysis using Software Gradistat are 2 types of sediment, namely medium sand & fine sand and 2 types of sediment texture, namely Slightly Gravelly Sand and Slightly Gravelly Muddy Sand. The average percentage of seagrass cover at the intertidal station was 23.33 % while at the subtidal station it was 61.11% and only 2 species of seagrass were found, namely Enhalus acoroides and Halophila ovalis. The average density of seagrass at the intertidal station is 48.88 ind/m2 while at the subtidal station it is 86 ind/m2. The results of the Independent T-test analysis showed that there were significant differences in the cover and density of seagrass in the intertidal zone and subtidal zone in the coastal waters of Labakkang.